Komunikasi Kiai Pesantren - Samsul Arifin (Proceedings of Annual Conference for Muslim Scholars, 2018)
Focus of writing: communication model, ie stages and techniques in conveying messages in empowering the former rogue community from the perspective of counseling communication. This research uses qualitative approach of ethnography type. Data comes from documents and fieldnotes. Steps of data analysis: data reduction, display data, and conclusion drawing.Results: communication stages performed by kiai, stage of establishing, developing relationships, interventions, and follow-up. The technique of delivering messages by way of targhib (giving a life-long guarantee, to arouse interest and passion) and convey a message according to their language, so that the message according to their level of understanding (worldview) and empathic so that the messages can touch the bottom of their hearts.